Role of Election Management body in India after Independence - Dr. Rajni Arora, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
India is the largest democratic country in the world. On 26 January 1950, India has adopted constitution and gave the ideal of liberty, equality and justice for all people of India. Voting is essential part of any Democratic nation. It is backbone of democracy and Government is legitimated by elections. It maintains link between government and people of the state. People enjoy their political rights through elections. It helps to solve the problem of leadership competition. These representatives should work for the welfare of their people. Election can ensure a change in leadership. Election is means of self evolution after five years. Leaders can review their performance and try to fulfill the demands of citizens by elections that are conducted time to time.